2013
DOI: 10.1186/1297-9716-44-82
|View full text |Cite
|
Sign up to set email alerts
|

Innate sensing of viruses by pattern recognition receptors in birds

Abstract: Similar to mammals, several viral-sensing pattern recognition receptors (PRR) have been identified in birds including Toll-like receptors (TLR) and retinoic acid-inducible gene I (RIG-I)-like receptors (RLR). Avian TLR are slightly different from their mammalian counterparts, including the pseudogene TLR8, the absence of TLR9, and the presence of TLR1La, TLR1Lb, TLR15, and TLR21. Avian TLR3 and TLR7 are involved in RNA virus recognition, especially highly pathogenic avian influenza virus (HPAIV), while TLR15 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
125
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 99 publications
4
125
0
Order By: Relevance
“…The activation of PRRs by viral nucleic acids triggers the expression of innate antiviral genes such as interferon (Chen et al, 2013). In the present study, TLR3 was slightly decreased in the early stage of infection and was slightly increased in late stage that may trigger the down-regulation of IFN-a mRNA expression, as TLR3 plays two-faced role in the induction of antivirus IFN-a or IFN-b in different situation (Okahira et al, 2005;Kogut et al, 2005).…”
Section: Discussionsupporting
confidence: 49%
“…The activation of PRRs by viral nucleic acids triggers the expression of innate antiviral genes such as interferon (Chen et al, 2013). In the present study, TLR3 was slightly decreased in the early stage of infection and was slightly increased in late stage that may trigger the down-regulation of IFN-a mRNA expression, as TLR3 plays two-faced role in the induction of antivirus IFN-a or IFN-b in different situation (Okahira et al, 2005;Kogut et al, 2005).…”
Section: Discussionsupporting
confidence: 49%
“…As RIG-I is absent in chickens, IFIH1 is a functional compensate16. Avian TLRs are different from their mammalian counterparts, lacking TLR9 but possessing TLR1LA, poultry-specific TLR15, and a TLR9 homologue TLR2117. TLR3 and TLR7 are known to be involved in RNA virus recognition, and its stimulation leads to activation of IRF3 and IRF7 (IFN-regulatory factor 3 and 7).…”
mentioning
confidence: 99%
“…TLR3 and TLR7 are known to be involved in RNA virus recognition, and its stimulation leads to activation of IRF3 and IRF7 (IFN-regulatory factor 3 and 7). These factors then signal IFN transcription to trigger IFN-stimulated genes (ISGs) through JAK-STAT pathway to express various antiviral proteins151718. A global gene expression profiling of chicken kidney has revealed that 103 immune and inflammatory-related genes are involved in the host defense response during the first week of IBV infection19.…”
mentioning
confidence: 99%
“…IFIH1 and DDX58 can distinguish different RNA viruses and play a crucial role in host antiviral responses . Previous studies also suggested that IFIH1 and DDX58 can identify RNA viruses in the cells via binding to the pathogen‐associated molecular pattern . The current study recruited 3065 participants to investigate the effect of the IFIH1 rs3747517 and DDX58 rs9695310 on the susceptibility and clinical outcome of HCV infection, with a statistical power of 0.964.…”
Section: Discussionmentioning
confidence: 99%